A Guide to Bone Marrow Transplantation - Deeg, H. Joachim; Klingemann, Hans-Georg; Phillips, Gordon L. (Springer Berlin Heidelberg, 1992)
In 1988 we presented our Guide to Bone Marrow Transplan tation. The reception has been enthusiastic and we have re ceived a flood of critical comments, suggestions and requests to provide an update in due time. Although several books on marrow transplantation have recently been published, their scope and goal have generally been different. Hence, we have decided to prepare a second edition of the Guide. Our aim was to maintain a short, concise text which never theless would incorporate changes that have occurred over the past four or five years. We have streamlined the description of pretransplant considerations, by condensing two sections into one (Treatment Planning and Timing of Transplantation). This also facilitated the review of controversial indications for marrow transplantation, for example in patients with acute myelogenous leukemia in first chemotherapy-induced remission. We have updated the chapter dealing with conditioning regimens and have expanded the section on donor selection, in particular in regard to the current level of tissue typing and the identification of unrelated volunteer donors. In the chapter on collection, processing, and infusion of marrow, we have incorporated recent developments, for example, the use of closed systems for marrow harvesting and processing and the use of solid phase separation of stem cells
Keywords: Hematology; Oncology; General Surgery; Oncology; Surgery; Knochenmarktransplantation; Aufsatzsammlung